Treatment Outcome Assessment of the Pharmacist-Managed Quit Smoking Clinic in Malaysia. (5th December 2014) - Shafie, Asrul Akmal; Hassali, Mohamed Azmi; Rabi, Rudy; Lee, Mei Lin
Abstract : Introduction: Evaluating a new health service is different from evaluating a new drug, as the former depends on the local delivery structure and culture. No data are available on the effectiveness of the existing pharmacist-managed quit smoking clinic (PM-QSC) in Malaysia. We evaluated the effectiveness in terms of the quit and default rate, the cost per quitter, cost per patient and the number of days of the patient remained in the managed care of the pharmacist. Methods: The patients' medical records at the PM-QSC in a tertiary hospital in Melaka, Malaysia, were examined retrospectively from January 2009 to December 2010. Patients were grouped into current smokers, attempted to quit and quitters. Costs were calculated per patient visit on the basis of resource used (smoking cessation agents (SCAs)) and the personnel involved (time spent by the pharmacist). This study was reviewed and approved by the Malaysia Research Ethics Committee (MREC). Results: The quit rate between January 2009 and December 2010 was 5.8%, and the default rate was 71.8%. The average quit period for all smokers enrolled was 298 days. From the health provider perspective, the average costs per quitter, per patient and per quit attempt were MYR 953.28 (USD 308), MYR 55.71 (USD 18) and MYR 34.74 (USD 11), respectively. Conclusion: The pharmacist delivery of cessation services at a public-funded QSC was associated with a high default rate. The pharmacist could not be dismissed entirely as an ineffective health care professional (HCP) for the provision of the cessation service based solely on this preliminary data, but these findings stress the need to address the high default rate prior to the expansion of the service.